Analisis Pembelajaran Bahasa Indonesia Melalui Metode Tanya Jawab Materi Teks Eksplanasi Pada Siswa Kelas VI SDN Koranji 2 Pulosari - Husniah Husniah; Yeni Sulaeman (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
This research was motivated by the Indonesian language learning process for grade 6 students in elementary schools. In the process, all explanations, both material and learning media at SDN Koranji 2 Pulosari. This research uses a qualitative descriptive method by collecting data using library research as well as direct observation when learning to read explanatory texts takes place at SDN Koranji 2 Pulosari. Based on the results of observations, researchers found that Indonesian language learning was carried out through the question and answer method. All Indonesian language material is given by teachers to students through independent assignments. Students submit independent assignments to determine the extent to which they understand the explanatory text. There are still students who do not fully understand the material provided by the teacher. This depends on the level of difficulty of the Indonesian language learning material provided directly. However, students still try to understand the material by asking questions or discussing. Thus, it can be concluded that the Indonesian language learning process through the question and answer method given by the teacher during the learning process for class VI students at SDN Koranji 2 Pulosari went quite well.